The role academic platforms in combating antimicrobial resistance (amr) in conjuction with world amr awareness(waaw) 2025 "act now:protect our present,secure our future" - Jamal, Janattul Ain; Muda, Mohd Rahimi (Faculty of Pharmacy, 2025)
Antimicrobial resistance (AMR) remains one of the most pressing and complex public health challenges of the modern era. The World Health Organization (WHO) has warned that AMR threatens to reverse decades of medical progress, potentially ushering in a post-antibiotic era where common infections could once again become fatal. To address this escalating crisis, WHO, established the World Antimicrobial Resistance Awareness Week (WAAW) every year from 18th to 24th November, to raise awareness and promote coordinated global action against AMR. The 2025 theme, “Act Now: Protect Our Present, Secure Our Future” highlights the significant need for collective commitment to preserve the effectiveness of existing antimicrobials and safeguard future generations.